2017
DOI: 10.1155/2017/4897258
|View full text |Cite
|
Sign up to set email alerts
|

Blood Vessel Extraction in Color Retinal Fundus Images with Enhancement Filtering and Unsupervised Classification

Abstract: Retinal blood vessels have a significant role in the diagnosis and treatment of various retinal diseases such as diabetic retinopathy, glaucoma, arteriosclerosis, and hypertension. For this reason, retinal vasculature extraction is important in order to help specialists for the diagnosis and treatment of systematic diseases. In this paper, a novel approach is developed to extract retinal blood vessel network. Our method comprises four stages: (1) preprocessing stage in order to prepare dataset for segmentation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 27 publications
(38 reference statements)
0
20
0
8
Order By: Relevance
“…The second was published in the 1950s by Dr. Paul Tower. He confirmed that each retina in each eye has a different blood vessels pattern and also using photographs he showed that even identical twins have different pattern in their retinas" (Yavuz & Cemal, 2017).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The second was published in the 1950s by Dr. Paul Tower. He confirmed that each retina in each eye has a different blood vessels pattern and also using photographs he showed that even identical twins have different pattern in their retinas" (Yavuz & Cemal, 2017).…”
Section: Introductionmentioning
confidence: 91%
“…This unique blood vessels patterns form the foundation of the retinal recognition system. "There are two famous studies that confirmed the unique blood vessel pattern found in the retina" (Yavuz & Cemal, 2017):…”
Section: Introductionmentioning
confidence: 98%
“…Bharkad used top hat, a morphological operator with three different structuring elements [24]. Yavuz et al enhanced the retinal image using Gabor, Frangi, and Gaussian filters, followed by the use of top hat transform and clustering mechanism for segmenting the blood vessels [25].…”
Section: Related Workmentioning
confidence: 99%
“…two-dimensional matched filter response (2D MFR)), morfologinis metodas, kraujagyslių sekimo metodas. Prie mašininio mokymosi metodų priskiriami k-NN, SVM, Bayesian decision rule, Fuzzy C-means, K-means (Yavuz, Köse, 2017) ir dirbtiniai neuroniniai tinklai.…”
Section: Akies Vaizdų Semantinis Segmentavimasunclassified